New attack on Kotzig's conjecture - Christian Barrientos; Sarah M. Minion (Electronic Journal of Graph Theory and Applications (EJGTA), 2016)
In this paper we study a technique to transform $α $-labeled trees into $ρ $-labeled forests. We use this result to prove that the complete graph $K_{2n+1}$ can be decomposed into these types of forests. In addition we show a robust family of trees that admit $ρ $-labelings, we use this result to describe the set of all trees for which a $ρ $-labeling must be found to completely solve Kotzig's conjecture about decomposing cyclically the complete graph $K_{2n+1}$ into copies of any tree of size $n$.